2019
DOI: 10.3390/fermentation5030060
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Native Non-Saccharomyces Yeasts with Biocontrol Activity against Spoilage Yeasts in Order to Produce Healthy Regional Wines

Abstract: Two major spoilage yeasts in the wine industry, Brettanomyces bruxellensis and Zygosaccharomyces rouxii, produce off-flavors and gas, causing considerable economic losses. Traditionally, SO2 has been used in winemaking to prevent spoilage, but strict regulations are in place regarding its use due to its toxic and allergenic effects. To reduce its usage researchers have been searching for alternative techniques. One alternative is biocontrol, which can be used either independently or in a complementary way to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 55 publications
2
38
0
Order By: Relevance
“…In addition, biocontrol strategies for the limitation of undesired microbial growth in foods and beverages by the application of non-Saccharomyces yeasts have been highlighted in recent years [66,67]. Berbegal et al [68] reported that the use of a mixed starter of different strains of S. cerevisiae or a mix of specific strains of non-Saccharomyces yeast with S. cerevisiae are efficient strategies in the control of the spoilage yeast like Brettanomyces bruxellensis and the volatile phenols' production in wine.…”
Section: Sensory Evaluations Of Citrus Winesmentioning
confidence: 99%
“…In addition, biocontrol strategies for the limitation of undesired microbial growth in foods and beverages by the application of non-Saccharomyces yeasts have been highlighted in recent years [66,67]. Berbegal et al [68] reported that the use of a mixed starter of different strains of S. cerevisiae or a mix of specific strains of non-Saccharomyces yeast with S. cerevisiae are efficient strategies in the control of the spoilage yeast like Brettanomyces bruxellensis and the volatile phenols' production in wine.…”
Section: Sensory Evaluations Of Citrus Winesmentioning
confidence: 99%
“…Thus, it was hypothesized that the use of W. anomalus starter cultures can partially replace SO 2 during grape must fermentation, in order to reduce the wine sulfite content; antimicrobial activity was also reported toward other minor yeast species present during the early stages of grape fermentation, such as Pichia guilliermondii or Pichia membranifaciens [17,42]. Moreover the potential use of the purified toxin Pikt from W. anomalus D2 as an alternative to sulfur dioxide (SO 2 ) has been proposed because Pikt, unlike SO 2 , produced irreversible damage on sensitive yeasts, ensuring the complete control of spoilage Brettanomyces yeasts [42,47,49].…”
Section: Non-saccharomyces Yeasts Producing Antimicrobial Compoundsmentioning
confidence: 99%
“…Fermentation temperature: The strain WTC016 was cultured overnight to the stationary phase (OD 600 = 2.0), and then inoculated as 1% inoculum in 50 mL of liquid LB broth with 1% inoculum in 250 mL flask and fermented at different temperature conditions starting from 26,28,30,32,34,36,38, and 40 • C, and shaken at 250 rpm for 36 h. The NK concentration was then measured after the fermentation.…”
Section: Single-factor Experiments To Optimize Fermentation Conditionmentioning
confidence: 99%